Smart Devices and Systems for Vibration Sensing and Energy Harvesting - Tao, Kai; Li, Yunjia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on state-of-the-art vibration sensing and energy harvesting technologies. The 11 chapters can be divided into three aspects: (i) new materials for vibration energy harvesting applications, (ii) design and fabrication of vibration energy harvesters (VEHs), and (iii) system-level integration and testing of VEHs.